Higher environmental temperatures promote acceleration of spermatogenesis in vivo in mice (Mus musculus). (October 2018) - Costa, Guilherme M.J.; Lacerda, Samyra M.S.N.; Figueiredo, André F.A.; Leal, Marcelo C.; Rezende-Neto, José V.; França, Luiz R.
Abstract: Temperature is considered a crucial modulator of reproductive activity and testis homeostasis. It is well known that elevated temperatures cause several effects on testicular components, particularly on germ cells, which might lead to the impairment of spermatogenesis and loss of male fertility. The present study aimed to evaluate the effects of different environmental temperatures on several morphofunctional testis parameters, with emphasis on duration of spermatogenesis and spermatogenic efficiency. Thirty sexually mature Swiss mice ( Mus musculus ) were allocated in three different experimental groups, being kept in vivarium for three weeks at 16 °C, 23 °C (control group) and 32 °C. In order to estimate the duration of spermatogenesis, three animals per each group received intraperitoneal injections of tritiated thymidine and the testes were perfused-fixed and routinely processed for histological, morphometrical and immunoperoxidase analyses. Although the lower temperature (16 °C) did not change most of the evaluated testicular parameters, our findings showed that higher environmental temperature (32 °C) is able to alter important testis parameters, resulting for instance in acceleration of spermatogenesis, alterations in the stages frequencies, increased number of germ and Leydig cells apoptosis and reduced Sertoli cell and spermatogenic efficiencies. As in many conditions infertile men exhibit higher mean scrotal temperature, we believe that experimental studies with mice involving temperature might represent an interesting approach to better understand the mechanisms related to human testis function and sperm production. Highlights: Germ cell pace is accelerated in vivo under higher environmental temperatures. Higher environmental temperatures promote germ and Leydig cells apoptosis. Daily sperm production is reduced in mice kept at higher environmental temperatures. Testicular parameters kept unaltered under lower environmental temperatures.